Associations Between Microsatellite Markers and Traits Related to Performance, Carcass and Organs in Chickens - Boschiero, C.; Rosario, M.F.; Ledur, M.C.; Campos, R.L.R.; Ambo, M.; Coutinho, L.L.; Moura, A.S.A.M.T. (International Journal of Poultry Science, 2009)
Associations between four microsatellite markers on chromosome 11 and five on chromosome 13 with performance, carcass and organs traits were investigated in chickens using a least-squares approach applied to single-marker analysis. Three hundred and twenty seven F2 chickens from the EMBRAPA broiler x layer experimental population were evaluated for 16 traits: five related to performance, five to carcass and five to organs, plus the hematocrit. Two significance thresholds were considered: p